2015
DOI: 10.2138/am-2015-5155
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the [Na/(Na+K)] ratio on Fe speciation in phonolitic glasses

Abstract: Natural iron-bearing sodic phonolitic melts represent an extreme compositional range of the effect of the [Na/(Na+K)] ratio on the geochemical behavior of Fe in volcanic systems. Yet phonolitic melts have not been well investigated. The glasses studied here have been synthesized from liquids equilibrated over a range of oxygen fugacity conditions [log10(fO2) from –0.68 to –11] to elucidate the role of the alkali ratio in influencing the local environment around both divalent and trivalent Fe. In this study, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
2

Relationship

7
0

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 48 publications
(87 reference statements)
4
19
0
1
Order By: Relevance
“…For example, Mysen et al [259] reported a slight decrease of the slope according to the ionic potential of the alkaline-earth cation in alkaline-earth silicate glasses. This trend is corroborated by the recent result of Cicconi et al [260], who observed that the mean ionic field strength of the alkali metal cations influence the slope of the log # k vs log ( mU k. mU n. ) relationship in multicomponent glasses.…”
Section: Temperature Oxygen Fugacity and Pressure Effectssupporting
confidence: 82%
See 2 more Smart Citations
“…For example, Mysen et al [259] reported a slight decrease of the slope according to the ionic potential of the alkaline-earth cation in alkaline-earth silicate glasses. This trend is corroborated by the recent result of Cicconi et al [260], who observed that the mean ionic field strength of the alkali metal cations influence the slope of the log # k vs log ( mU k. mU n. ) relationship in multicomponent glasses.…”
Section: Temperature Oxygen Fugacity and Pressure Effectssupporting
confidence: 82%
“…Regarding the local environment of Fe in silicate glasses, data on simplified and multicomponent systems, often, are contradictory. Ferric iron is mainly regarded as 4-fold coordinated, although higher coordination numbers have been also reported [260,269,[287][288][289][290][291][292][293][294][295][296][297][298]. Regarding Fe 2+ , its structural environment is even more debated.…”
Section: Compositional Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the redox perspective, iron plays different roles depending on its oxidation state (Mysen and Richet 2005;Cicconi et al 2015 and references therein): Fe 2+ acts as a network-modifier, whereas Fe 3+ plays a more complex role that will be discussed later. Given the abundance of iron in melts, Fe 3+ /Fe 2+ exchanges can have dramatic effects on melt structure and properties.…”
Section: Composition and Structure: Who Controls What?mentioning
confidence: 99%
“…The ferric-ferrous ratio of equilibrated silicate melts depends on the temperature, redox state, and the chemical composition (including the volatile content) of the melt (Kress and Carmichael 1991;Mysen 1991;Ottonello et al 2001;Botcharnikov et al 2005;Moretti 2005;Giuli et al 2012;Borisov et al 2015;Cicconi et al 2015). Thus a precise quantification of the ferric-ferrous ratio in silicate melts and glasses is a crucial constraint for the adequate parameterization of both the composition-dependence of physical properties (e.g., liquid viscosity and density) and the redox conditions prevailing in magmatic systems.…”
Section: Introductionmentioning
confidence: 99%